Pengaruh Karakter Wirausaha Dan Keunggulan Bersaing Terhadap Keberhasilan Wirausaha Pada UMKM Sapu Ijuk Desa Medan Senembah Tanjung Morawa - wana mulyana; Wan Dian Safina (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2022)
This research was conducted to find out whether there is an influence between entrepreneurial character and competitive advantage on entrepreneurial success in SMEs broom fibers. In this study, the authors used descriptive and quantitative analysis with a sample of 35 MSME workers broom fibers in the village of Medan, Senembah, Tanjung Morawa. This research was conducted by distributing questionnaires to the UMKM workers of palm fiber brooms in the village of Medan, Senembah, Tanjung Morawa. The research that has been done shows the results that entrepreneurial character factors and competitive advantage have an influence on entrepreneurial success in palm fiber SME's as shown from the results of multiple regression Y = 5.605 + 0.524X1 + 0.181X2 + e. The results of the partial test (t test) of entrepreneurial character on entrepreneurial success in MSMEs obtained a tcount = 3.209> 1.69 and a partial test value (t test) for competitive advantage obtained a tcount= 1.220> 1.69, these results indicate that partially Entrepreneurial character and competitive advantage have a positive and significant impact on entrepreneurial success in SME broom fibers, besides the F test results obtained Fcount>Ftable (16,438>3,295) with a probability level (0.01<0.05). The value of the coefficient of determination (R2) of 0.507 means that the entrepreneurial character and competitive advantage are able to increase entrepreneurial success in the Micro, Small and Medium Enterprises (SMEs) broom fibers in Medan Senebah Tanjung Morawa village by 50.7% and the remaining 49.3% is explained by other variables outside the study.